K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(=\dfrac{2^{12}\cdot3^4\left(3-1\right)}{2^{12}\cdot3^6}-\dfrac{5^{10}\cdot7^3\left(1-7\right)}{5^9\cdot7^3+5^9\cdot7^3\cdot2^3}\)

\(=\dfrac{-2}{9}-\dfrac{5\cdot\left(-6\right)}{9}=\dfrac{-2-5\cdot\left(-6\right)}{9}=\dfrac{-2+30}{9}=\dfrac{28}{9}\)

29 tháng 5 2018

\(A=\frac{1}{1\cdot2}+\frac{2}{2\cdot4}+\frac{3}{4\cdot7}+\frac{4}{7\cdot11}+...+\frac{10}{46\cdot56}\)

\(A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+...+\frac{1}{46}-\frac{1}{56}\)

\(A=1-\frac{1}{56}\)

\(A=\frac{55}{56}\)

\(B=\frac{4}{3\cdot7}+\frac{4}{7\cdot11}+\frac{4}{11\cdot15}+...+\frac{4}{23\cdot27}\)

\(B=\frac{1}{3}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{15}+...+\frac{1}{23}-\frac{1}{27}\)

\(B=\frac{1}{3}-\frac{1}{27}\)

\(B=\frac{8}{27}\)

\(C=\frac{4}{3\cdot6}+\frac{4}{6\cdot9}+\frac{4}{9\cdot12}+...+\frac{4}{99\cdot102}\)

\(C=\frac{4}{3}\left(\frac{3}{3\cdot6}+\frac{3}{6\cdot9}+\frac{3}{9\cdot12}+...+\frac{3}{99\cdot102}\right)\)

\(C=\frac{4}{3}\left(\frac{1}{3}-\frac{1}{6}+\frac{1}{6}-\frac{1}{9}+\frac{1}{9}-\frac{1}{12}+...+\frac{1}{99}-\frac{1}{102}\right)\)

\(C=\frac{4}{3}\left(\frac{1}{3}-\frac{1}{102}\right)\)

\(C=\frac{4}{3}\cdot\frac{33}{102}\)

\(C=\frac{22}{51}\)

29 tháng 5 2018

Các bạn giải giúp mình nha😐

26 tháng 3 2017

\(P=\frac{1}{1.2}+\frac{2}{2.4}+\frac{3}{4.7}+...+\frac{10}{46.56}\)

\(P=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{46}-\frac{1}{56}\)

\(P=1-\frac{1}{56}\)

\(P=\frac{55}{56}\)

21 tháng 4 2017

a, \(\dfrac{62}{7}.x=\dfrac{29}{90}.\dfrac{3}{56}\)

\(\dfrac{62}{7}.x=\dfrac{29}{1680}\)

\(x=\dfrac{29}{1680}:\dfrac{62}{7}\)

\(x=\dfrac{29}{14880}\)

b, \(\dfrac{1}{5}:x=\dfrac{1}{5}-\dfrac{1}{7}\)

\(\dfrac{1}{5}:x=\dfrac{2}{35}\)

\(x=\dfrac{1}{5}:\dfrac{2}{35}\)

\(x=\dfrac{7}{2}\)

c, \(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\left(2+\dfrac{1}{6}-\dfrac{1}{4}\right)=\dfrac{7}{46}\)

\(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\left(\dfrac{13}{6}-\dfrac{1}{4}\right)=\dfrac{7}{46}\)

\(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\dfrac{23}{12}=\dfrac{7}{46}\)

\(\left(x+\dfrac{-1}{12}\right):\dfrac{23}{12}=\dfrac{7}{46}\)

\(\left(x+\dfrac{-1}{12}\right)=\dfrac{7}{46}.\dfrac{23}{12}\)

\(x+\dfrac{-1}{12}=\dfrac{7}{24}\)

\(x=\dfrac{7}{24}-\dfrac{-1}{12}\)

\(x=\dfrac{3}{8}\)

28 tháng 3 2018

\(\frac{1}{1\cdot2}+\frac{2}{2\cdot4}+\frac{3}{4.7}+..........+\frac{10}{46.56}\)

\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{7}+........+\frac{1}{46}-\frac{1}{56}\)

\(=1-\frac{1}{56}\)

\(=\frac{55}{56}\)

a: =-48+27+56-48-27-36

=-96+20

=-76

b: =23-57+57-33=-10

c: =-98+12-159-12-41

=-98-200

=-298

11 tháng 1 2022

Cảm ơn bạn